Chemical Exchange Saturation Transfer (CEST) Imaging: Description of Technique and Potential Clinical Applications - Kogan, Feliks (2013)
Chemical exchange saturation transfer (CEST) is a magnetic resonance imaging (MRI) contrast enhancement technique that enables indirect detection of metabolites with exchangeable protons. Endogenous metabolites with exchangeable protons including many endogenous proteins with amide protons, glycosaminoglycans (GAG), glycogen, myo-inositol (MI), glutamate (Glu), creatine (Cr) and several others have been identified as potential in vivo endogenous CEST agents. These endogenous CEST agents can be exploited as non-invasive and non-ionizing biomarkers of disease diagnosis and treatment monitoring. This review focuses on the recent technical developments in endogenous in vivo CEST MRI from various metabolites as well as their potential clinical applications. The basic underlying principles of CEST, its potential limitations and new techniques to mitigate them are discussed.